Hubungan Tingkat Pengetahuan Tindakan Phacoemulsifikasi Dengan Kecemasan Pada Pasien Katarak Di Rumah Sakit Mata Solo - Wahyuningtyas, Septia Putri; , Agus Sudaryanto, S.Kep., Ns., M.Kes (2016)
Abstract The healthy of our eyes is very important becauses of our sight can't be replace by anything the disease of eyes can be classify to some category, one of blindness causes in this world is cataract. Cataract is turbid condition on ocular, based on study report prevalence of cataract is causes aging on over 65-74 years old as many as 50%. The cataract treatment with surgery that is phacoemulsifikasi method. This surgery is use ultrasonography that does not need many scam on cornea or anterior sclera. But the peoples knowledge and their attitude in Indonesia to their healthy eyes and cataract treatment is very less by phacoemulsifikasi method. The purpose of this research is to knowing the relationship between knowledge level of phacoemulsifikasi method and anxiety for cataract's patients at Eye Hospital of Surakarta (Solo). This research was used quantitative, with descriptive analytic and cross sectional method. The research subjec all of cataract's patients in 45-80 years old as much as 97 respondents by used accidental sampling. The analysis was used Spearman Rank (Rho) with significance level (α = 0,05) and p value 0,001 (p<0,05) so Ho was denied and Ha was accepted. The results showed of this research a relationship between knowledge level of phacoemulsifikasi and anxiety for cataract's patients at Eye Hospital of Solo. The suggestions for Eye Hospital Solo can be provide the means to provide health education prior to cataract surgery with phacoemulsifikasi, so can detract anxiety when they confront cataract's surgery. Keywords : knowledge, phacoemulsifikasi, anxiety, cataract.